Sex and the city Season 5 - Parker, Sarah Jessica; Cattrall, Kim.; Davis, Kristin, 1966-; Nixon, Cynthia; Noth, Christopher, 1954-; Corbett, John, 1961-; Garson, Willie, 1964-; Eigenberg, David, 1964-; MacLachlan, Kyle, 1960-; Dryburgh, Stuart; Stanford, Kate.; Cuomo, Douglas J.; et al. ([United States] : Home Box Office, 2003)
The women of Sex and the city have new loves, new responsibilities, new choices to make, and - oh yeah - a new baby to deal with, and that equates to a whole new outlook on being single in New York City.
Originally released as a television series - fifth season from 2002-2003.
Based on the the character created by Darren Star and the novel by Candace Bushnell.
Director of photography, Stuart Dryburgh ... [et al.] ; editor, Kate Stanford ; original music, Douglas J. Cuomo ; costume designer, Ellen Lutter ; production designer, Mark Friedberg.
Sarah Jessica Parker, Kim Cattrall, Kristin Davis, Cynthia Nixon, Chris Noth, John Corbett, Willie Garson, David Eigenberg, Kyle MacLachlan.
MPAA rating: Not rated.
DVD.
Keywords: Journalists -- Drama; Women -- Sexual behavior -- Drama; New York (N.Y.) -- Social life and customs -- Drama; Television comedies; Video recordings for the hearing impaired